PERANCANGAN SISTEM INFORMASI MANAJEMEN DOKUMEN PROYEK DENGAN METODE PROTOTYPE BERBASIS WEB - Faiz Dwi Darmawan; Zulhalim Zulhalim; Akmal Budi Yulianto; Hidayatul Ichwan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The rapid advancement of information technology requires companies to have an effective and efficient project document management system. PT. Lintas Teknologi Indonesia faces several challenges in managing project documents, such as the absence of a centralized system, difficulty in tracking project progress, and the risk of document loss or duplication. This research aims to develop a web-based project document management information system to address these issues. The method used is prototyping, involving steps such as requirements gathering, prototype creation, evaluation, coding, testing, and system implementation. The system is designed using Laravel and MySQL technologies, and tested using the black-box method to ensure that each function operates as expected. The final result is a web application that enables centralized storage of project documents, access sharing between users (admin and engineer), and real-time tracking of project status. This system is expected to improve project team efficiency and minimize errors in the document management process.